Responses of sorne Nigerian vegetables to plant growth regulator treatments - Kadiri, M; Mukhtar, Fatimah; Adejare Agboola, David (Revista de Biología Tropical, 1996)
The effects of single and combined growth regulator treatments of indole-3-acetic acid (IAA), gibberellic acid (GA3) and coconut milk on plant height, yield, chlorophyIl and vitamin contents of Abelmoschus esculetus L and Solanum gilo L were investigated. The single growth regulator treatments consisted of 50mglL, l00mglL of IAA and GA3 and 10%, 15% of coconut milk. In case of combined growth regulator treatments, the treatments were 100mg/L IAA + 100mglL GA3,IOOmglL ¡AA + 15% coconut milk and lOOmglL GA3 + 15% coconut milk. Control vegetable plants were sprayed with water. Single treatments of lOOmglL IAA,IOOmglL GA3’ 10% and 15% coconut milk resulted in significantly increased plant height, chlorophyIl contents and yield of A. esculentus, H. sabdarijJa and S. gilo while only conbined treatments of 100mglL IAA + 10% coconut milk and lOOmglL GA3 + 15% coconut milk had such an effect on A. esculentus and S.gilo but not on H. sabdarijJa. Moreover, singletreatments of IOOmglL GA3 and 15% coconut milk caused significantIy higher vitamins A, B6 and C contents of treated plants whereas the combined treatments produced such an effect on only vitamin C contents oi treated plants. Growth regulator treatments of 100mglL GA3 and 15% coconut milk were consistentIy the best out of the entire growth regulator treatments tried with the treated plants having the greatest plant height, yield, chlorophyIl and vitamin C contents.